Sipadan and Ligitan Island Sovereignty Disputes: Foreign Policy Analysis of Indonesia and Malaysia In Resolving International Conflicts - Pascal Amadeo Yapputro; Aurel Aprilia Annisya Trisetya; Jocelyn Cheriesta (Publikasi Indonesia, 2023)
Initially, the state had full and exclusive jurisdiction over its territory. The main definition of international relations is the shared needs of one country with another, because a country cannot meet its own needs. There are international relations that have a positive impact, but it is not uncommon for disputes and conflicts to arise. The Sipadan and Ligitan Island cases are an international dispute between Malaysia and Indonesia related to the issue of state sovereignty and international relations. This study aims to analyze the foreign policies of Indonesia and Malaysia in the settlement of disputes over the sovereignty of Sipadan and Ligitan Islands. The method used is normative juridical research by collecting data from primary and secondary sources. The results of the study show that Indonesia and Malaysia have made various efforts to resolve the dispute, but this conflict is still ongoing and affects bilateral relations between the two countries. Therefore, further cooperation is needed between the two countries to find a mutually acceptable solution to this dispute.